2020
DOI: 10.1371/journal.pone.0231239
|View full text |Cite
|
Sign up to set email alerts
|

Detection of microbial cell-free DNA in maternal and umbilical cord plasma in patients with chorioamnionitis using next generation sequencing

Abstract: Background Chorioamnionitis has been linked to spontaneous preterm labor and complications such as neonatal sepsis. We hypothesized that microbial cell-free (cf) DNA would be detectable in maternal plasma in patients with chorioamnionitis and could be the basis for a non-invasive method to detect fetal exposure to microorganisms. Objective The purpose of this study was to determine whether next generation sequencing could detect microbial cfDNA in maternal plasma in patients with chorioamnionitis. Study design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…blood, urine, cerebrospinal fluid) before initiation of antibiotic therapy, obtaining sufficient quantity of blood for culture, and investigation of viral and fungal etiologies should allow comfort in discontinuation of antibiotics if cultures are sterile [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] . Ultimately, genomic methods for detection of microbial pathogens in body fluids may allow optimal identification of infected infants and more appropriate use of antimicrobial therapy [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…blood, urine, cerebrospinal fluid) before initiation of antibiotic therapy, obtaining sufficient quantity of blood for culture, and investigation of viral and fungal etiologies should allow comfort in discontinuation of antibiotics if cultures are sterile [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] . Ultimately, genomic methods for detection of microbial pathogens in body fluids may allow optimal identification of infected infants and more appropriate use of antimicrobial therapy [ 59 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Witt et al reported the detection of relevant microbial cf-DNA in maternal plasma of patients with chorioamnionitis. Their results may contribute to the development of a non-invasive assay for the detection of fetal exposure to microorganisms that would be useful to reduce complications from early neonatal sepsis [ 64 ]. Apart from blood, other body fluids may also contain microbial cf-DNA that may have clinical value.…”
Section: Cell-free Microbial and Viral Dnamentioning
confidence: 99%
“…Recent reports indicate that NGS measuring microbial cfDNA is useful in the diagnosis of cases of Streptococcus pneumoniae-related hemolytic uremic syndrome, Coxiella burnetii endocarditis, invasive Mycobacterium chimaera infection, Nocardia cyriacigeorgica pneumonia, Capnocytophaga canimorsus sepsis, M. tuberculosis complex and M. haemophilum infections, M. bovis aortitis; Candida spp., Aspergillus spp., non-Aspergillus molds invasive infections; Pneumocystis jirovecii pneumonia (PJP), Toxoplasma gondii infection and chorioamnionitis, among others 24,[26][27][28][29][30][31][32][33] . Among 21 patients with culture-positive infective endocarditis, cfDNA NGS identified the same organism as blood cultures in 20 patients (95% sensitivity) and additionally identified Enterococcus faecalis in one out of the three patients with definitive culture-negative endocarditis 34 .…”
Section: Introductionmentioning
confidence: 99%